2015
DOI: 10.1007/s13157-015-0676-9
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of MODIS Spectral Indices for Monitoring Hydrological Dynamics of a Small, Seasonally-Flooded Wetland in Southern Spain

Abstract: Monitoring spatio-temporal dynamics of hydrology in seasonally-flooded wetlands is important for water management and biodiversity conservation. Spectral data and derived indices from t he Moderate Resolution Imaging Spectroradiometer (MODIS) have been used for hydrological monitoring of large wetlands. However, comparable studies for small wetlands (<25 km 2) are lacking. Our aims are to examine whether MODIS-derived indices at 500-m spatial resolution can perform this task for small wetlands, and to compare … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
53
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 51 publications
(58 citation statements)
references
References 79 publications
4
53
0
1
Order By: Relevance
“…This study tentatively confirms what previous studies have already revealed globally: that wetlands are declining in area and quality (McCarthy et al, 2007;Junk et al, 2013;Davidson, 2014;Gardner et al, 2015;Li et al, 2015). Although not conclusive, as the decline may be due to climatic variability and indeed in 2015 the region was severely affected by the El Niño-associated drought event (Rembold et al, 2016;FAO, 2016), the methodology managed to detect both seasonal variation (Figs 4 and 5) and also a trend showing deterioration.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This study tentatively confirms what previous studies have already revealed globally: that wetlands are declining in area and quality (McCarthy et al, 2007;Junk et al, 2013;Davidson, 2014;Gardner et al, 2015;Li et al, 2015). Although not conclusive, as the decline may be due to climatic variability and indeed in 2015 the region was severely affected by the El Niño-associated drought event (Rembold et al, 2016;FAO, 2016), the methodology managed to detect both seasonal variation (Figs 4 and 5) and also a trend showing deterioration.…”
Section: Discussionsupporting
confidence: 92%
“…These include; blue (459-479 nm), green (545-565 nm), red (620-670 nm), near infrared (841-876 nm), and shortwave infrared (SWIR1: 1 230-1 250 nm, SWIR2: 1 628-1 652 nm, SWIR3: 2 105-2 155 nm). The MODIS MCD43 500-m resolution reflectance datasets, which remove view-angle effects, mask cloud cover and reduce atmospheric contamination (Li et al, 2015), were used for this study.…”
Section: Satellite and Dem Data Download And Analysismentioning
confidence: 99%
See 3 more Smart Citations